Quantitative Imaging of FRET-Based Biosensors for Cell- and Organelle-Specific Analyses in Plants. (16th February 2016) - Banerjee, Swayoma; Garcia, Luis Rene; Versaw, Wayne K.
Abstract: Genetically encoded Förster resonance energy transfer (FRET)-based biosensors have been used to report relative concentrations of ions and small molecules, as well as changes in protein conformation, posttranslational modifications, and protein–protein interactions. Changes in FRET are typically quantified through ratiometric analysis of fluorescence intensities. Here we describe methods to evaluate ratiometric imaging data acquired through confocal microscopy of a FRET-based inorganic phosphate biosensor in different cells and subcellular compartments of Arabidopsis thaliana. Linear regression was applied to donor, acceptor, and FRET-derived acceptor fluorescence intensities obtained from images of multiple plants to estimate FRET ratios and associated location-specific spectral correction factors with high precision. FRET/donor ratios provided a combination of high dynamic range and precision for this biosensor when applied to the cytosol of both root and leaf cells, but lower precision when this ratiometric method was applied to chloroplasts. We attribute this effect to quenching of donor fluorescence because high precision was achieved with FRET/acceptor ratios and thus is the preferred ratiometric method for this organelle. A ligand-insensitive biosensor was also used to distinguish nonspecific changes in FRET ratios. These studies provide a useful guide for conducting quantitative ratiometric studies in live plants that is applicable to any FRET-based biosensor.